In Vivo and In Vitro Study of a Polylactide-Fiber-Reinforced β-Tricalcium Phosphate Composite Cage in an Ovine Anterior Cervical Intercorporal Fusion Model - Janek Frantzén; Aliisa Pälli; Esa Kotilainen; Harri Heino; Bettina Mannerström; Heini Huhtala; Hannu Kuokkanen; George K. Sándor; Kari Leino; Matias Röyttä; Riitta Parkkola; Riitta Suuronen; et al. (International Journal of Biomaterials)
A poly-70L/30DL-lactide (PLA70)–β-tricalcium phosphate (β-TCP) composite implant reinforced by continuous PLA-96L/4D-lactide (PLA96) fibers was designed for in vivo spinal fusion. The pilot study was performed with four sheep, using titanium cage implants as controls. The composite implants failed to direct bone growth as desired, whereas the bone contact and the proper integration were evident with controls 6 months after implantation. Therefore, the PLA70/β-TCP composite matrix material was further analyzed in the in vitro experiment by human and ovine adipose stem cells (hASCs and oASCs). The composites proved to be biocompatible as confirmed by live/dead assay. The proliferation rate of oASCs was higher than that of hASCs at all times during the 28 d culture period. Furthermore, the composites had only a minor osteogenic effect on oASCs, whereas the hASC osteogenesis on PLA70/β-TCP composites was evident. In conclusion, the composite implant material can be applied with hASCs for tissue engineering but not be evaluated in vivo with sheep.